Journal for the Study of Antisemitism Contemporary Antisemitism and Racism in the Shadow of the Holocaust (Special Issue) - Stoegner, Karin; Bechter, Nicolas; Klaff, Lesley; Spencer, Philip (Academic Studies Press, 2021)
This Special Issue of the Journal for the Study of Antisemitismcontains a collection of papers that were presented at the InternationalConference "Contemporary Antisemitism and Racism in the Shadow of theHolocaust"-the midterm conference of the Research Network on EthnicRelations, Racism and Antisemitism within the European SociologicalAssociation. The network was set up over a decade ago with the aim ofaddressing what was felt to be a serious gap in contemporary social theory,the continuing and indeed growing presence of antisemitism and itsconnection to other racisms.